Pengaruh Kombinasi Pupuk Kompos dan NPK Terhadap Pertumbuhan, Jumlah Klorofil A dan Kadar Air Gracilaria verrucosa [Effect Of Compost and NPK Fertilizer Combinations On Growth, Chlorophyll A and Water Content Of Gracilaria verrucose] - Mochammad Amin Alamsjah; Iva Nur Silviana; Kadek Rachmawati (Faculty of Fisheries and Marine Universitas Airlangga, 2009)
AbstractIn general, Gracilaria culture still using organic and inorganic fertilizer single. Organic or inorganic fertilizer applied is felt have not yet enough to support the growth of Gracilaria. The aim of this experiment was to know the best compost and NPK combinations which could influence on growth, chlorophyll a and water content of G.verrucosa. Treatment applied was compost and NPK combinations with different doses, that is A treatment (0 gr/l : 2 gr/l), B treatment (0,5 gr/l : 1,5 gr/l), C treatment (1 gr/l : 1gr/l), D treatment (1,5 gr/l : 0,5 gr/l), E treatment (2 gr/l : 0 gr/l) and F treatment (without fertilizer), each treatment was replicated 4 times. Main parameter observed was daily growth rate (%/day), relative length growth (%), chlorophyll a (í¬g/ml) and water content (%) of G.verrucosa. oSupported parameter observed was pH, temperature ( C) and salinity (